Why Beauty Matters. (2nd January 2018) - Scruton, Roger
Abstract: Judgments of beauty are neither subjective nor arbitrary, and are a necessary part of practical reasoning in any attempt to harmonise our activities and ways of life with those of our neighbours. The creation of a neighbourhood, a place, a home, or any other settlement in which people of different occupations and views reside side by side involves coordination of a kind that only aesthetic judgment can reliably achieve. And that is why judgment of that kind exists, and why a rational being who has no grasp of it is incapacitated.